Effect of baker's yeast Saccharomyces cerevisiae in a feed mixture contaminated with aflatoxins on histological indicators of the liver and kidney of broilers - مصطفى, عمار (Submission and Review of Research -Biological Sciences Series, 2025)
This study aimed to evaluate the effect of adding the yeast Saccharomyces cerevisiae to feed contaminated with aflatoxins on some histological indicators of the liver and kidneys of broilers. (120) one-day-old unsexed chicks of the hybrid (Ross-308) were used, with an average weight of 42.45 g. The birds were randomly divided into four experimental groups with three replicates for each group (10 birds for each replicate). Group T1 (negative control) received an uncontaminated basal diet with no additives. Group T2 (positive control) was fed a diet naturally contaminated with aflatoxins produced by Aspergillus flavus. Groups T3 and T4 received the contaminated diet supplemented with 0.1% and 0.2% S. cerevisiae, respectively. The results showed a better improvement in the histological indicators in the T4 group, as the liver tissues showed an almost similar appearance to the T1 negative control group (p ≥ 0.05), with a significant decrease in renal tissue degenerations, in the T4 group birds compared to the T2 positive control group.